Microevolution of the mexT and lasR Reinforces the Bias of Quorum Sensing System in Laboratory Strains of Pseudomonas aeruginosa PAO1 - Liu, Yang; Ahator, Stephen Dela; Wang, Huishan; Feng, Qishun; Xu, Yinuo; Li, Chuhao; Zhou, Xiaofan; Zhang, Lian-Hui (Frontiers in Microbiology, 2022)
The Pseudomonas aeruginosa strain PAO1 has routinely been used as a laboratory model for quorum sensing (QS). However, the microevolution of P. aeruginosa laboratory strains resulting in genetic and phenotypic variations have caused inconsistencies in QS research. To investigate the underlying causes of these variations, we analyzed 5 Pseudomonas aeruginosa PAO1 sublines from our laboratory using a combination of phenotypic characterization, high throughput genome sequencing, and bioinformatic analysis. The major phenotypic variations among the sublines spanned across the levels of QS signals and virulence factors such as pyocyanin and elastase. Furthermore, the sublines exhibited distinct variations in motility and biofilm formation. Most of the phenotypic variations were mapped to mutations in the lasR and mexT, which are key components of the QS circuit. By introducing these mutations in the subline PAO1-E, which is devoid of such mutations, we confirmed their influence on QS, virulence, motility and biofilm formation. The findings further highlight a possible divergent regulatory mechanism between the LasR and MexT in the P. aeruginosa. The results of our study reveal the effects of microevolution on the reproducibility of most research data from QS studies and further highlight mexT as a key component of the QS circuit of P. aeruginosa.